EFFECT OF TRANSACTIONAL AND TRANSFORMATIONAL LEADERSHIP STYLE, MOTIVATION AND COMPETENCE TO PERFORMANCE OF EMPLOYEES PT. SANJAYATAMA LESTARI - Oktora, Jublina; Rizan, Mohammad; Situngkir, Sihol (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
In this study, the objective is to conduct a systematic examination Effect of Transactional and Transformational Leadership Style, Motivation and Competence to Employee Performance PT. Sanjayatama Lestari. The samples used were employees of PT. Sanjayatama Lestari the number of respondents as many as 95 people. The analysis used is multiple linear regression. This study examined five variables: Transactional Leadership Style (X1), Transformational Leadership Style (X2), motivation (X3) and Competence (X4) as the independent variable and the performance (Y) as the dependent variable. Partial test shows that the transactional leadership style influenced by 3.876 (positive and significant) on the performance. Transformational leadership style also influenced significantly by 3.128. Furthermore, the motivation also has a significant influence amounted to 4.210 and the latter is the competence of significant influence amounted to 6.283. Keywords: transactional leadership style, transformational leadership style, motivation, competence, performance and multiple linear regression.